(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2025)
The study aims to demonstrate the importance of applying the International Financial Reporting Standards (IAS), and to identify the extent of the ability of Iraq companies to apply international standards and to identify the obstacles that prevent this, it also aimed primarily to study the requirements of Iraq companies to adopt and apply the International Financial Reporting standards (IFRS8) related to by identifying the operating sectors and its role in measuring and disclosing them in sector report, and the extent of its ability to provide appropriate information that helps users of financial statements to make the right and appropriate decisions. To achieve the objectives of the study and answer its questions, the researcher followed the deductive approach on the theoretical side, and the inductive approach on the applied side. Finally the study reached a set of conclusions, the most important of which are; The adoption of the international Accounting and Financial Reporting Standards (IAS), and thus further improve the quality of accounting information and enhance the role of integrity and financial control. 2.The application of the international Financial Reporting Standards (IFRS8) work to disclose the information that users need Sector information is an essential management tool that enables management to monitor performance and allocate Resources and business strategy development.